2018
DOI: 10.1007/s11357-018-0017-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of curcumin for age-associated cognitive decline: a narrative review of preclinical and clinical studies

Abstract: Processes such as aberrant redox signaling and chronic low-grade systemic inflammation have been reported to modulate age-associated pathologies such as cognitive impairment. Curcumin, the primary therapeutic component of the Indian spice, Turmeric (Curcuma longa), has long been known for its strong anti-inflammatory and antioxidant activity attributable to its unique molecular structure. Recently, an interest in this polyphenol as a cognitive therapeutic for the elderly has emerged. The purpose of this paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 102 publications
2
48
0
1
Order By: Relevance
“…Even though this is never the case, it can en-courage some people to stop if they get properly started, particularly when the first few weeks of any diet are the hardest. According to the extremely small consumption of carbohydrate-less than 50 -60 grams each day-ketogenic-diets could therefore never be ideal for those who choose to run off on a holiday [8] Many studies approved that the ketogenic diet has different effects on health, this was shown in Table 1. There was a marked increase in the weight of mice who were feeding rodent ketogenic diet while a marked decrease in the mice occurred who were feeding on high fats containing ketogenic diet…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though this is never the case, it can en-courage some people to stop if they get properly started, particularly when the first few weeks of any diet are the hardest. According to the extremely small consumption of carbohydrate-less than 50 -60 grams each day-ketogenic-diets could therefore never be ideal for those who choose to run off on a holiday [8] Many studies approved that the ketogenic diet has different effects on health, this was shown in Table 1. There was a marked increase in the weight of mice who were feeding rodent ketogenic diet while a marked decrease in the mice occurred who were feeding on high fats containing ketogenic diet…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Most people eat a high-carb diet, and the body uses sugar for food. There have been glucose issues [8]. The body will store around two-thousand calories of glucose storage at any period throughout the type of glucose.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Along with antioxidant properties, this polyphenol compound exhibit anti-inflammatory, anti-neurodegenerative and anticancer activities (Sarker and Franks, 2018). The potential of curcumin in preventing and treating various agingassociated pathological conditions has been repeatedly reported (Sundar et al, 2018).…”
Section: Nano-curcuminmentioning
confidence: 99%
“…Curcumin has been investigated in various animal models of cognitive decline including models of accelerated and normal ageing and dementia using different study designs, with benefits observed in most studies (Sanei & Saberi-Demneh, 2019;Sarker & Franks, 2018;Williams et al, 2011). Its antioxidant mechanisms explain its ability to improve memory in many of these studies, including via reduced oxidative damage through enhancing glutathione (GSH) and decreasing lipid peroxide levels in brain tissue Sarker & Franks, 2018;Williams et al, 2011).…”
Section: Turmericmentioning
confidence: 99%
“…Curcumin has been investigated in various animal models of cognitive decline including models of accelerated and normal ageing and dementia using different study designs, with benefits observed in most studies (Sanei & Saberi-Demneh, 2019;Sarker & Franks, 2018;Williams et al, 2011). Its antioxidant mechanisms explain its ability to improve memory in many of these studies, including via reduced oxidative damage through enhancing glutathione (GSH) and decreasing lipid peroxide levels in brain tissue Sarker & Franks, 2018;Williams et al, 2011). Animal studies also show curcumin improves memory tasks and it can reverse stress-induced reductions in neurogenesis, associated with brain-derived neurotrophic factor (BDNF; Poulose, Miller, Scott, & Shukitt-Hale, T A B L E 1 Nutraceutical phytochemicals with relevance to cognition in normal and pathological brain ageing EGCG -Antioxidant and neuroprotective against oxidative stress via elevation of mRNA expression of γ-glutamylcysteine ligase to increase cellular GSH, stimulation of PKC and modulation of cell cycle genes (Williams et al, 2011) -Activates α7 nicotinic receptors and signalling molecules P13K and AKT to suppress Bcl-2 down-regulation (Howes & Simmonds, 2014) -Inhibits AChE, is anti-inflammatory via different mechanisms and inhibits neuroinflammatory response of microglia to Aβ (Cascella et al, 2017) -Inhibits βand γ-secretase activities (Costa et al, 2017;Williams et al, 2011) Epicatechin -Increases GSH levels in astrocytes -Improves memory by ameliorating lipid peroxidation and ROS in rats with Aβ-induced hippocampal toxicity (Williams et al, 2011) Cocoa flavanols -Enhance expression of neuroprotective and neuromodulatory proteins (Sokolov et al, 2013) -Improve angiogenesis and cerebral blood flow in the brain (Dominguez & Barbagallo, 2018) Green tea -Epidemiological evidence suggests regular intake reduced age-related cognitive decline and dementia risk (Williams et al, 2011) -Intake (2 g daily for 3 months in an RCT) improved cognitive performance ( affect global cognition or memory (Zhou et al, 2018) Caffeoylquinic acids (including chlorogenic acid)…”
Section: Turmericmentioning
confidence: 99%